Analisis Kemampuan Berpikir Kritis Siswa dalam Memecahkan Masalah pada Kelas IV Sekolah Dasar. - Ayunda Fitri Milenia; Mu’jizatin Fadiana; Heny Sulistyaningrum (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Critical thinking is an important skill that needs to be developed from elementary school. This study aims to analyze the critical thinking skills of fourth-grade students in solving problems on the topic "Becoming an Environmental Hero." The study used a descriptive qualitative approach with data collection techniques through essay tests and interviews. The analysis of critical thinking skills was based on Perkins and Murphy's indicators, namely clarification, assessment, inference, and strategy. The results showed that students' critical thinking skills were in various categories and relatively low. Most students experienced difficulties in the clarification and assessment stages, which resulted in low ability to draw conclusions and determine problem-solving strategies. These findings demonstrate the need for contextual and process-oriented learning to develop elementary school students' critical thinking skills.